Thermal Comfort Findings: Scenario At Malaysian Automotive Industry - Ahmad Rasdan, Ismail; Shashi Kumar, S A Karagaratnan; K., Kadirgama (National Library of Serbia, 2013)
This paper discusses the findings of thermal comfort assessment at Malaysian automotive industry. Nine critical workstations were chosen as subjects for the study in order to determine the thermal comfort among workers at Malaysian automotive industry. The human subjects for the study comprises of the operators from tire receiving,dashboard assembly, drum tester, body assembly, seat assembly, door check assembly, stamping workstation, engine sub assembly, and paint shop of the factory. The environmental factors such as wet bulb globe temperature, relative humidity, air velocity, illuminance were measured using BABUC A apparatus and thermal comfort measurement equipment. Through questionnaire survey, the demographic data of subjects and their perceptions on thermal comfort at each workstation were assessed based on ISO Standard 7730 and thermal sensation scale using predicted mean vote. Then, predicted percentage of dissatisfied is used to estimate the thermal satisfaction of occupants. The results indicated that most of the workstations of the automotive industry are considered as uncomfortable. Tire receiving station is considered having better working environment compared to other stations with lowest predicted mean vote index of 1.09 to 1.41 and predicted percentage of dissatisfied of 46%. Meanwhile, the engine sub assembly station and paint shop of assembly are considered the worst thermal environment with the predicted mean vote index values ranging between 2.1 to 2.9 and predicted percentage of dissatisfied values of 81% to 99%. Therefore, these two workstations are considered not comfortable because the thermal sensation scale is warm and almost hot.